The Israel Boycott Movement: The Role of The Theory of Planned Behavior on Purchase Intention of Israel-Affiliated Products with Religiousness As a Moderator - Aya Sofia Ardelia; Faishol Luthfi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the influence of the theory of planned behavior, which consists of attitudes, subjective norms, and behavioral control, on the intention in purchasing Israeli-affiliated products. This study will also analyze how religiosity moderates this influence. Primary data from 170 people will be collected using purposive sampling and analyzed using Structural Equation Modelling (SEM). The results show that perceived subjective norms and behavioral control influence the intention in purchasing Israeli-affiliated goods. Furthermore, religiosity is not able to moderate (strengthen/weaken) the relationship between attitudes, subjective norms and perceived behavioral control towards the purchase of Israeli-affiliated goods. Religiosity is actually a factor that directly influences the purchase of Israeli-affiliated goods.